A location model for the departure port tax rebate policy. Issue 24 (20th May 2020) - Chen, Zigen; Xin, Xu; Chen, Kang; Zeng, Qingcheng
ABSTRACT: In this paper, a bi-level programming model is established to solve the decision problem of the departure port tax rebate policy (DPTRP). Based on the theory of user equilibrium, the model can optimize the selection of inland port (or domestic trade port) to implement the DPTRP with the goal of maximizing total generalized transportation cost under the constraint of the existing total construction investment. Based on genetic algorithm, a new algorithm is developed to solve the model, and numerical experiments are carried out using north-eastern China as the research object. The results show that the implementation of the DPTRP will reduce the tax refund time and cost of north-eastern China.